Pelatihan Penyusunan Kajian Akademik dan RAB dalam Penilaian Merger, Konsolidasi, dan Akuisisi bagi Pelaku Usaha dengan Komisi Pengawas Persaingan Usaha (KPPU) - Meher, Montayana; Nasution, Alvin Hamzah; Lubis, Mhd Ansor; Kurniati, Agata (Abdimas Indonesian Journal, 2025)
The low understanding of business actors on the preparation of academic studies, financial analysis, and calculation of Cost Budget Plans (RAB) in the merger, consolidation, and acquisition (MKA) process is an obstacle in making accurate and regulatory business decisions. This community service activity aims to increase the capacity of business actors in compiling comprehensive academic studies and RAB as the basis for assessing the feasibility of MKA. The implementation method includes classroom training, study preparation simulation, case study analysis, and guided technical assistance. The results of the activity showed a significant increase in participants' understanding of legal, economic, and financial aspects in MKA, as well as the ability to prepare more structured analytical documents. This activity is expected to strengthen business literacy and encourage more professional corporate governance.